Girls should be Girls: The Impact of Child Marriage on Human Development - Guimarães, Raquel Rangel de Meireles; Julião, Nayara Abreu; Doria, Thaila Renata Teixeira (UNESC, 2020)
Child marriage is a violation of Human Rights and an impediment to social and economic development, it is strongly rooted in gender inequality. In Brazil, this practice has a predominantly informal and consensual quality, they often involve adult men married to girls in early puberty. The objective of this study is to synthesize the literature on the impact of child marriage on the most diverse indicators of human development - such as education, labor market, health, fertility, violence and female empowerment. In summary, the literature reveals that child marriage has a negative impact on these indicators, and this corroborates the urge to eliminate this phenomenon, which will ensure women’s right to a full economic and social life.